Prognostic Factors and Outcomes in Elderly Patients with Acute Cardiovascular Events - A Retrospective Analysis - ASHRAF, MARYAM ASHRAF; RAZA, MUHAMMAD ZAHID ALI RAZA; ALTAF, FAIZA ALTAF; ANWAR, MAIDA ANWAR; CHAUDHARY, ARSALAN ASLAM CHAUDHARY; SIDDIQUE, AAMIR SIDDIQUE (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Elderly patients presenting with acute cardiovascular events (ACVEs) often have higher mortality from atypical symptoms, comorbidities, and delayed treatment. Prognostic markers need to be accurately identified in order to improve outcomes. Aim: To assess the prognostic factors and clinical outcomes of elderly patients (≥ 65 years) admitted with ACVEs at a tertiary care hospital in Pakistan. Methods: This retrospective observational study of 100 patients over age 65 years with acute myocardial infarction, acute heart failure, or unstable angina. Demographics, comorbidities, biomarkers, echocardiographic parameters, treatment timelines, and outcomes were analyzed. Independent predictors of in-hospital mortality were determined by performing multivariate logistic regression. Results: Mean age was 74.1 ± 6.3 years, and male patients were 56%. In hospital mortality was 17 per cent, and 29 per cent were readmitted within six months. The LVEF <40% (OR 3.4; p<0.001), NT-proBNP >1800 pg/mL (OR 2.9; p=0.003), age >75 years (OR 2.6; p=0.008), serum creatinine >1.5mg/dL (OR 2.1; p=0.021) and PCI delay > 90 minutes (OR 1.7; p=0.042) were found to be independent predictors of mortality. Reduction of mortality risk by beta blockers was significant (OR 0.59, p=0.021). Conclusion: Elderly patients with ACVEs have high mortality, especially in the presence of reduced LVEF and renal impairment, as well as delayed PCI. Beta-blocker therapy is protective. Identification of these prognostic factors in early stages can improve outcomes, especially in resource-constrained settings.